Polish Regulations on Platform Work de lege ferenda from the Perspective of the European Union Law - Mitrus, Leszek (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The present elaboration is dedicated to the EU draft Directive on improving working conditions in platform work, and its potential implications for Polish labour law. Author introduces the planned amendments on employment status of platform workers, including the legal presumption on employment relationship, and new provisions on employment conditions for platform workers.